ISLAMIC CHARACTER EDUCATION IN INDONESIAN NATIONAL CURRICULA: A CRITICAL POLICY ANALYSIS OF THE 2013 AND MERDEKA FRAMEWORKS - Alhamuddin, Alhamuddin (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
Character education has been a national agenda in Indonesia since the early 2010s. It was formally integrated into the 2013 Curriculum and further strengthened through the Merdeka Curriculum, which was launched in 2022. This study aims to examine how character education is conceptualized and implemented within these two curricula, particularly through the lens of Islamic religious education. Using a qualitative content analysis approach, the study analyzes key policy documents issued by the Ministry of Education, including competency standards, learning outcomes, and the Pancasila Student Profile. The analysis reveals that both curricula explicitly emphasize core values such as faith, discipline, nationalism, integrity, and critical thinking as integral components of students' character formation. These values are embedded within the formulation of core competencies and learning indicators across various subjects. However, pedagogical implementation guidelines remain limited and normative, often relying on broad and vague terms like “value internalization,” without being supported by concrete and contextual teaching strategies. Furthermore, both curricula tend to adopt a top-down and moralistic tone, providing limited space for dialogic, reflective, or participatory approaches. In addition, teachers are burdened with numerous administrative tasks, which reduces their time and focus on developing students’ character in an optimal way. The study concludes that in order to achieve effective character education within Indonesia’s diverse context, clearer, more inclusive pedagogical strategies rooted in critical student engagement are needed. The findings also imply the necessity for teacher training and curriculum development that are more responsive to social realities and students' needs.